2015
DOI: 10.1002/hep.27424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sofosbuvir and ribavirin treatment on peripheral and hepatic lipid metabolism in chronic hepatitis C virus, genotype 1–infected patients

Abstract: Hepatitis C virus (HCV) modulates intrahepatic cholesterol biosynthetic pathways to promote viral replication. Chronic HCV infection is associated with altered metabolism, including dyslipidemia and insulin resistance, which contributes to disease progression and influences response to therapy. To further understand the impact of HCV infection on host metabolism, we examined changes in serum lipid profiles and intrahepatic expression of lipid-related genes during interferon (IFN)-free treatment of chronic HCV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
149
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 48 publications
20
149
2
2
Order By: Relevance
“…Based on these results, the role of metabolic factors as predictors of the DAAs has decreased or even ameliorated. Also, the changes in lipid profile after therapy represented an interesting finding, as recently reported with the use DAAs [12,16]. We found a significant reduction in serum triglycerides and a significant elevation of serum cholesterol, LDL, HDL, and LDL/HDL ratio at 12 weeks post-treatment.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Based on these results, the role of metabolic factors as predictors of the DAAs has decreased or even ameliorated. Also, the changes in lipid profile after therapy represented an interesting finding, as recently reported with the use DAAs [12,16]. We found a significant reduction in serum triglycerides and a significant elevation of serum cholesterol, LDL, HDL, and LDL/HDL ratio at 12 weeks post-treatment.…”
Section: Discussionsupporting
confidence: 84%
“…The direct link between HCV and host lipoproteins explicates the significant interrelationship between HCV and host lipid metabolism, as proved both in vitro [17] and in clinical studies [12]. Meissner et al [12] reported a concomitant decrease in triglycerides and VLDL particle size and a marked increase in serum LDLc after 24 weeks of treating HCV genotype 1 infected patients with SOF/RBV, irrespective of the treatment outcome [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to their expectation, our work showed a marked increase in IR at EOT ( Table 2). Meissner et al, also reported no improvement of IR after treatment with DAA despite lowering of HbA1c in non-diabetic patients [20].…”
Section: Discussionmentioning
confidence: 97%